2014
DOI: 10.1177/1358863x14559589
|View full text |Cite
|
Sign up to set email alerts
|

Development of administrative data algorithms to identify patients with critical limb ischemia

Abstract: Administrative data have been used to identify patients with various diseases, yet no prior study has determined the utility of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM)-based codes to identify CLI patients. CLI cases (n=126), adjudicated by a vascular specialist, were carefully defined and enrolled in a hospital registry. Controls were frequency matched to cases on age, sex and admission date in a 2:1 ratio. ICD-9-CM codes for all patients were extracted. Algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…If CLI specific procedure codes (amputation, revascularization) were added, the sensitivity was even higher (92%). 28 For amputation detection, another publication reported a sensitivity value of 94.4%, 29 which is similar or superior to other disease conditions. 28 As for the comorbidity, the application of disease classification codes (ICD) alone leads to grater uncertainty; 30 therefore, a more complex algorithm of ICD codes for case detection, like the definition of diabetes, was applied.…”
Section: Discussionmentioning
confidence: 95%
“…If CLI specific procedure codes (amputation, revascularization) were added, the sensitivity was even higher (92%). 28 For amputation detection, another publication reported a sensitivity value of 94.4%, 29 which is similar or superior to other disease conditions. 28 As for the comorbidity, the application of disease classification codes (ICD) alone leads to grater uncertainty; 30 therefore, a more complex algorithm of ICD codes for case detection, like the definition of diabetes, was applied.…”
Section: Discussionmentioning
confidence: 95%
“…Other codes such as 707.14 (ulcer of heel and midfoot) or 785.4 (gangrene), with or without associated procedure codes, could have justifiably been used. However, the addition of procedure codes has been shown to reduce sensitivity and overall agreement when applied to well‐qualified CLI patients 27. Because there are no universally accepted ICD‐9‐CM codes to identify CLI and that the focus of this study was not to determine CLI incidence, but to characterize clinical outcome following diagnosis, a focused list of ICD‐9‐CM codes for CLI diagnosis was used to limit bias introduced by inclusion of cases with unrelated conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous literature, 15,16 clinical PAD in this study was identified based on hospitalizations with the following IInternational Classification of Diseases (ICD)-9 discharge codes: 440.20 (atherosclerosis of native arteries of the extremities, unspecified); 440.21 (atherosclerosis of native arteries of the extremities with intermittent claudication); 440.22 (atherosclerosis of native arteries of the extremities with rest pain); 440.23 (atherosclerosis of native arteries of the extremities with ulceration); 440.24 (atherosclerosis of native arteries of the extremities with gangrene); 440.29 (other atherosclerosis of native arteries of the extremities); 440.3 (atherosclerosis of bypass graft of the extremities); 440.4 (chronic total occlusion of artery of the extremities); 38.18 (endarterectomy, lower limb arteries); 39.25 (aorta-iliac-femoral bypass); 39.29 (other (peripheral) vascular shunt or bypass); and 39.50 (angioplasty or atherectomy of other non-coronary vessel(s)).…”
Section: Outcome Assessmentmentioning
confidence: 99%